HISTORIOGRAPHY OF VIEWS OF NATIONAL-PROGRESSIVE JADIDS OF TURKESTAN (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
The colonial system in Central Asia in the XIX-XX centuries despite its strict boundaries, social and political shifts took place under the influence of world integration processes, and the movement of national-progressive intellectuals to renew and reform society became an impetus for the formation and development of modernism. Studies on this topic show that the Jadidism movement was a very strong impetus for national self-awareness. The goal of the national intellectuals was to solve the problems of the society based on universal and national values and to find a way for the future development of the society. This article describes the historiography of Turkestan moderns' national views and services to independence.